NATIONAL IDEOLOGY IN THE INDEPENDENT STATES OF CENTRAL ASIA AND THE SOUTHERN CAUCASUS: ITS PHENOMENON, SPECIFICS, AND PROSPECTS - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2011)
The political processes underway in the independent Central Eurasian republics call in particular for a detailed analysis of the emergence, functioning, and development of their national ideologies. Throughout world history, no reform, modernization, or democratization during the formation and development of nations could have succeeded, nor can ever succeed, without majority support for a set of clearly formulated and desirable aims and easily grasped ideas. In fact, at all times, states with a national ideology left those states which rejected ideology as part of their policy far behind in every respect. The following fairly succinct comments are intended as an analysis of the past, present, and future of the national-ideological complexes in eight independent republics of Central Asia and the Southern Caucasus (including Georgia); they are compared with what is going on in this respect in other CIS countries (Russia, Belarus, and Ukraine).1 In view of the fundamental role of the state2 and weakness of civil society in practically all the CIS countries, I concentrated on the official position in the particular country, because it is this position, and not the alternative platform3 of the systemic and non-systemic opposition, that has so far attracted the attention of the academic and expert communities.